2010
DOI: 10.1073/pnas.0913709107
|View full text |Cite
|
Sign up to set email alerts
|

HJURP binds CENP-A via a highly conserved N-terminal domain and mediates its deposition at centromeres

Abstract: The human histone H3 variant, CENP-A, replaces the conventional histone H3 in centromeric chromatin and, together with centromerespecific DNA-binding factors, directs the assembly of the kinetochore. We purified the prenucelosomal e-CENP-A complex. We found that HJURP, a member of the complex, was required for cell cycle specific targeting of CENP-A to centromeres. HJURP facilitated efficient deposition of CENP-A/H4 tetramers to naked DNA in vitro. Bacterially expressed HJURP binds at a stoichiometric ratio to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
193
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(205 citation statements)
references
References 43 publications
(50 reference statements)
12
193
0
Order By: Relevance
“…4B, indicated with an asterisk on the right) emerges, and the intensity of this band is stronger at a 1:1 GST-HJURP CBD-to-CENP-A-H4 tetramer molar ratio than at higher concentrations of GST-HJURP CBD. The identity of this protein-DNA complex remains unknown, but its property is reminiscent of the previously suggested CENP-A-H4 tetrasomes (Shuaib et al 2010). Thus, disruption of the nonspecific association of the CENP-A-H4 tetramer with DNA may promote nucleosome assembly.…”
Section: Hjurp Prevents Spontaneous Association Of Dnamentioning
confidence: 91%
See 2 more Smart Citations
“…4B, indicated with an asterisk on the right) emerges, and the intensity of this band is stronger at a 1:1 GST-HJURP CBD-to-CENP-A-H4 tetramer molar ratio than at higher concentrations of GST-HJURP CBD. The identity of this protein-DNA complex remains unknown, but its property is reminiscent of the previously suggested CENP-A-H4 tetrasomes (Shuaib et al 2010). Thus, disruption of the nonspecific association of the CENP-A-H4 tetramer with DNA may promote nucleosome assembly.…”
Section: Hjurp Prevents Spontaneous Association Of Dnamentioning
confidence: 91%
“…It was shown previously that the CATD of CENP-A serves as a cis-acting element that confers the CENP-A specificity of centromere targeting and nucleosome assembly (Black et al 2004). In particular, a chimera protein of histone H3 carrying the CATD of CENP-A (H3 CATD ) was able to bind HJURP in vitro and in vivo (Foltz et al 2009;Shuaib et al 2010). Interestingly, among the 22 amino acids of CATD that are different between CENP-A and histone H3, only two residues in loop-1 (Asn 85 and Ala 88) and two residues in aA (Gln 89 and His 104) of CENP-A make direct interactions with HJURP.…”
Section: Specificity For Hjurp Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CATD is composed of the loop1 linker and α2-helix of CENH3 (28,29), and its substitution enabled the incorporation of an H3 chimera into centromeres (26). This domain mediates molecular recognition events before and after nucleosome assembly and is important for binding of CENH3 to centromeric DNA (27,28,30), to CENH3-specific chaperones (31)(32)(33), and to CENH3-stabilizing factors (34,35).…”
mentioning
confidence: 99%
“…HJURP (Holliday junction recognition protein) was originally named because it was suggested to bind Holliday junctions (Kato et al 2007) and was subsequently identified in purifications of soluble CENP-A complexes that represent a prechromatin assembly intermediate Foltz et al 2009). HJURP and Scm3 bind directly to a dimer of CENP-A and histone H4 through recognition of the CATD domain of CENP-A by HJURP/Scm3's conserved amino terminus (Foltz et al 2009;Shuaib et al 2010;Cho and Harrison 2011;Hu et al 2011;Zhou et al 2011). In addition, HJURP forms contacts with CENP-A outside of the CATD that enhance the stability of the HJURP:CENP-A:H4 complex (Bassett et al 2012).…”
Section: Hjurp: the Cenp-a Chaperonementioning
confidence: 99%